2013
DOI: 10.3109/09638237.2012.759193
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW ARTICLE Mental health economics: Insights from Brazil

Abstract: Economic analysis to evaluate interventions in mental health care is a relatively recent addition to the field of health economics; in Brazil, it is also considered a topic within Epidemiology research area. There have been an increased number of studies developed in high-income countries. However, there are fewer CE studies in low- and middle-income ones. Psychiatric disorders represent a significant burden in developing countries, where resources devoted to health care are even scarcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It may sound incoherent that LMICs, which should be saving money, are probably those that are wasting it most. 39 Recent studies have pointed out the necessity of cost-effectiveness studies for LMICs, 40 but, to the best of our knowledge, the present work is the first to show an advantageous economic option for a chronic disease which can be treated with MPH-IR even in low-resource settings. 41 In addition, our study demonstrated that, in LMICs, investments in such analyses can reveal a favorable scenario in contrast with wealthy countries.…”
Section: Discussionmentioning
confidence: 74%
“…It may sound incoherent that LMICs, which should be saving money, are probably those that are wasting it most. 39 Recent studies have pointed out the necessity of cost-effectiveness studies for LMICs, 40 but, to the best of our knowledge, the present work is the first to show an advantageous economic option for a chronic disease which can be treated with MPH-IR even in low-resource settings. 41 In addition, our study demonstrated that, in LMICs, investments in such analyses can reveal a favorable scenario in contrast with wealthy countries.…”
Section: Discussionmentioning
confidence: 74%
“…While we did not observe a relationship between SSRIs and prevalent CHD, we did observe a twofold increase association for SSRIs and coronary revascularization. A possible explanation for the null association between SSRIs and myocardial infarction is the restricted access to antidepressants from the SSRI class of antidepressants, resulting perhaps from the socioeconomic inequities of Brazilian mental health care ( 28 , 32 , 33 ) and high cost of these newer medications.…”
Section: Discussionmentioning
confidence: 99%
“…Many aspirational global goals have strong interdependencies with mental health, for example; peaceful and inclusive societies (Goodwin & Rona, 2013) and safety in human settlements (Ouanes et al, 2014), sustainable economic growth (Cruz et al, 2013) and productive employment (Katikireddi et al, 2012), inclusive education and learning opportunities, food security and improved nutrition (Surkan et al, 2011), maternal and child health, healthy lives and well-being, the overall population level (Guszkowska et al, 2014), and a more equal society.…”
Section: Mental Health Presents Cross-cutting Issues For Health and Dmentioning
confidence: 99%